2011
DOI: 10.1103/physrevb.84.155115
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical frustration effects on charge-driven quantum phase transitions

Abstract: The interplay of Coulomb repulsion and geometrical frustration on charge-driven quantum phase transitions is explored. The ground-state phase diagram of an extended Hubbard model on an anisotropic triangular lattice relevant to quarter-filled layered organic materials contains homogeneous metal, "pinball," and threefold charge ordered metallic phases. The stability of the pinball phase occurring for strong Coulomb repulsions is found to be strongly influenced by geometrical frustration. A comparison with a spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…1(b). As has been discussed in the context of the pinball liquid [31][32][33]40], arXiv:1305.6948v2 [cond-mat.str-el] …”
mentioning
confidence: 99%
“…1(b). As has been discussed in the context of the pinball liquid [31][32][33]40], arXiv:1305.6948v2 [cond-mat.str-el] …”
mentioning
confidence: 99%
“…This question, not simple enough, is later on studied by Cano-Cortes et al [31] in the extended Hubbard model at 3/4-filling, which approximately correspond to taking U ∞ from the tV -results and allow the double occupancy of electrons. Before discussing this issue, we overview the earlier works on the same extended Hubbard model, which are summarized in the phase diagram in Figure 10(a); the results of the exact diagonalization by Merino et al [32], VMC by Watanabe et al [33], and DMRG with by Nishimoto et al [34] are put together for comparison.…”
Section: E/n=v'/2mentioning
confidence: 99%
“…The latest exact diagonalization study by Cano-Cortes et al [31,38] finally concluded that the above three-fold charge ordered metallic state is not necessarily identified as a pinball liquid. As found in their phase diagram in Figure 11(a), the three-fold charge ordered state at smaller U and large V , which is identical to the one in Figure 10(a), is transformed to a pinball liquid state at larger U .…”
Section: E/n=v'/2mentioning
confidence: 99%
“…While these states are insulating, such exotic charge and magnetic orders become metallic away from the commensurate filling 4 . Furthermore, at quarter filling (n = 1/2), metallic states, named pinball liquids, have been also recently proposed [7][8][9][10] . They are characterized by a three-sublattice structure, in which the carriers of one sublattice are essentially localized (pins), with the remaining charges (balls) building an itinerant liquid on the interstitials.…”
Section: Introductionmentioning
confidence: 99%